Chippewa Indians smoking and tanning buck skins. / Ingersoll, Phot., Saint Paul - Ingersoll, T. W. (Truman Ward), 1862-1922 photographer. (William L. Clements Library, 1890)
Group portrait of three unidentified members of an Ojibwa Indian family (two women and a boy) wearing western clothing smoking and tanning deer hides in forest.; Original negative number?: 4092.; Printed on front bottom margin: Ingersoll, Photo., Saint Paul.; Printed on verso: New Illustrated Catalogue 100 Pages and over 60 Illustrations. Send 4 cents, Ingersoll's Artotype Printers Of Souvenirs, Commercial And Book Illustrations. Yellowstone Nat'l Park, Alaska, North Pacific Coast & Western Views.; Title derived from image caption.; "Ojibwa Indians" variant names: Anishinaabe, Chippewa Indians, Ojibwe Indians.